2016
DOI: 10.1152/ajpheart.00130.2016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coronary bifurcation morphology on wave propagation

Abstract: Validation of the proposed theory in multiple species reveals the equivalence between scaling laws and well-matchedness in the vasculature. Moreover, it captures the role of pulsatility in optimal vascular designs. This demonstrates the forward well-matchedness of coronary bifurcations, whereas backward waves are damped asymmetrically at junctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 78 publications
2
8
1
Order By: Relevance
“…Yet, branching was more symmetric and very asymmetric nodes occurred far less in the current human heart as compared to porcine hearts. For example, for large mother diameters (>500 µm) the median observed symmetry ratio was 0.59, in contrast to values below 0.40 for porcine data (VanBavel and Spaan, 1992;Kalsho and Kassab, 2004;Rivolo et al, 2016). Despite the same trend of increasing symmetry with decreasing diameter, this difference was found for all diameter classes, and at least for the larger diameter classes this cannot be attributed to the 30 µm resolution in the current study.…”
Section: Topologycontrasting
confidence: 81%
See 1 more Smart Citation
“…Yet, branching was more symmetric and very asymmetric nodes occurred far less in the current human heart as compared to porcine hearts. For example, for large mother diameters (>500 µm) the median observed symmetry ratio was 0.59, in contrast to values below 0.40 for porcine data (VanBavel and Spaan, 1992;Kalsho and Kassab, 2004;Rivolo et al, 2016). Despite the same trend of increasing symmetry with decreasing diameter, this difference was found for all diameter classes, and at least for the larger diameter classes this cannot be attributed to the 30 µm resolution in the current study.…”
Section: Topologycontrasting
confidence: 81%
“…Available anatomical studies address specific research questions and provide only limited data that do not allow a translation toward global coronary hemodynamics. This includes the vascularization of the anterior papillary muscle, perfused by the LCA versus RCA (Zajaczkowski et al, 2018), the impact of branching on wave propagation (Rivolo et al, 2016), the effect of side branches on coronary flow (Wiwatanapataphee et al, 2012), and branching patterns of only the large coronary arteries (Hutchins et al, 1976;Seiler et al, 1992;van der Waal et al, 2009;Schoenenberger et al, 2012;Cardenes et al, 2013;Gupta et al, 2013;Medrano-Gracia et al, 2017;Ormiston et al, 2018). In an initial study, we analyzed the presence of collateral connections within and between the perfusion territories in the human heart .…”
Section: Previous Datamentioning
confidence: 99%
“…Rumberger et al (1979) posited wave reflection as an explanation for prominent pressure and velocity oscillations observed in distal coronary arteries of the horse, while Arts et al (1979) concluded that, in dogs, frequencies below 7 Hz are reflected at the coronary peripheral resistance, whereas higher frequencies undergo minimal reflection. The study by Arts et al (1979), and in particular a recent detailed morphometric and theoretical study by Rivolo et al (2016), suggested that the major conduit coronary arteries are relatively well matched in the forward direction, as was assumed in the design of our 1D model. This implies that wave reflection occurs mainly in the small resistance arteries.…”
Section: Wave Reflection In Coronary Arteriesmentioning
confidence: 84%
“…(), and in particular a recent detailed morphometric and theoretical study by Rivolo et al . (), suggested that the major conduit coronary arteries are relatively well matched in the forward direction, as was assumed in the design of our 1D model. This implies that wave reflection occurs mainly in the small resistance arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study (15) of the coronary vasculature showed that 1D models attain similar haemodynamic predictions as 3D when using appropriate boundary conditions. Recent studies have analysed 1D systemic arterial models (10,16) to understand how uncertainty in network structure impacts haemodynamics. Fossan et.…”
mentioning
confidence: 99%